Time and cost optimization management in the field of urban excavation and coordination of drilling companies' performance using Geographic Information System (GIS) - Elham Khoshdel Pashaki (اکولوژی انسانی, 2023)
Today, urban facilities and services such as water, electricity, gas, telephone, and sewage are considered to be the main pillars of urban infrastructure, the lack of which disrupts the well-being of citizens. Therefore, considering the key role of infrastructure in shaping the urban form and landscape, optimal management of these facilities is essential to reduce physical deficiencies and increase citizen satisfaction. Due to the increasing needs for urban services, the exploitation of underground spaces has become inevitable and has gained special importance. Therefore, this research was conducted with the aim of designing and implementing a system based on Geographic Information System (GIS) and Web GIS to collect, organize, update, and share location-based data in the area between the Martyrs' Defender of the Holy Shrine Square and the Niayesh Unlevel Intersection in Rasht. The results of the study show that the implementation of an integrated location-based excavation system, while saving time and cost, provides a new platform for exchanging information, issuing reports, and permits between different institutions. Therefore, this web-based system, by utilizing the aforementioned technologies, simultaneously enables "excavation integration" and "time and cost optimization," and ultimately improves urban infrastructure management.